(untitled) (Journal of the College of Basic Education, 2024)
The world is currently witnessing a tremendous and remarkable development in various fields, which has been called the technical revolution. It has brought about major transformations represented in the Internet, digitization, and the ability to store information and ease of obtaining it. This revolution has contributed to governments and institutions reconsidering adopting the concept of digital transformation by replacing traditional processes with digital, and developing strategic plans to achieve its goals with high quality and efficiency. Digital leadership is defined as: a new method of administrative work that requires planning, organization, direction and control in order to continue progress through the optimal use of information and communications technology within the organization with the aim of developing its performance and providing services to beneficiaries at the lowest costs. An effective leader must be able to innovate, create, innovate, deal with variables efficiently, and be able to formulate goals and achieve them by adopting the elements of creativity and innovation, which in turn depend on the capabilities represented in (fluency, flexibility, originality, and sensitivity). He also has the ability to communicate between subordinates, which they all contribute to moving the organization towards the right direction, as innovation is considered an important factor in the organization’s success and achieving competitive advantage, and to create a sense of urgency and appropriate momentum around digital transformation, and to be able to overcome challenges and manage emergency crises effectively. Digital transformation includes a group of Technologies that are employed in organizations to varying degrees, including the Internet, artificial intelligence, digital platforms, machine learning, social media, and big data, and then various functional practices, and new competition mechanisms. From the above, the problem of the current research can be summarized by answering the following question: What are the implications of developing effective digital leadership in dealing with challenges and managing emergency crises? The importance of the research lies in: We are addressing a modern and important concept in the field of successful leadership. Today’s organizations are striving to keep pace with this digital transformation, which makes them competitive in the market to survive. This requires the presence of skilled leaders who are able to rethink how the organization and individuals use technology and processes and change and develop business performance, which is In effective digital leadership. The current research aims to identify the implications of developing effective digital leadership in dealing with challenges and managing emergency crises (a psychological vision). This goal will be achieved by addressing the following topics: The concept of digital leadership Dimensions and skills of effective digital leadership. Principles and models of digital leadership development. Interpreting the concept of effective leadership according to psychological theoretical frameworks. Strategies for developing and achieving successful digital leadership The challenges and crises facing effective leadership during the digital transformation journey. The implications of developing effective digital leadership in overcoming challenges and managing emergency crises The researchers used the descriptive analytical method as an approach to their research, and at the conclusion of the research, a number of conclusions, recommendations and proposals were presented to complete the scope of the current research.